DISTRIBUSI SEDIMEN PADA WADUK JATIBARANG, KOTA SEMARANG - Fitria Maya Lestari; Ratih Pujiastuti; Risdiana Cholifatul Afifah (Jurnal Teknik Indonesia, 2024)
The main issue in the operation of reservoirs is sedimentation. This can lead to silting and affect the reservoir's storage capacity. The distribution of sediments needs to be understood in order to gain an overview of their spread, so that measures can be taken to address sediment-related issues in the Jatibarang Reservoir. The analysis was conducted using sediment data from previous studies, which reported a total sediment volume of 6.64 million m³ over a period of 50 years. Based on topographic data, it was found that the Jatibarang Reservoir is classified as Type III, with a "hill" classification. The analysis results showed that the dimensionless factor F is 0.22, with a relative depth p of 0.53. Based on the sediment distribution analysis of the Jatibarang Reservoir with Empirical Area Reduction Method, it was found that after 50 years of operation, the new zero elevation of the reservoir would be at an elevation of +126.82 m. In comparison with the low water surface elevation at the existing dead storage of the Jatibarang Reservoir, which is at +136 m, it can be concluded that the Jatibarang reservoir can operate according to the planned lifespan and can still function for more than 50 years